2019
DOI: 10.3390/molecules24050834
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Electrospun Polymer Nanofibers with Diverse Morphologies

Abstract: Fiber structures with nanoscale diameters offer many fascinating features, such as excellent mechanical properties and high specific surface areas, making them attractive for many applications. Among a variety of technologies for preparing nanofibers, electrospinning is rapidly evolving into a simple process, which is capable of forming diverse morphologies due to its flexibility, functionality, and simplicity. In such review, more emphasis is put on the construction of polymer nanofiber structures and their p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
146
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 236 publications
(147 citation statements)
references
References 226 publications
(219 reference statements)
0
146
0
1
Order By: Relevance
“…Studies have shown that maneuvering the surface morphology of electrospun fibers (eg, crimped fibers, wrinkled fibers, porous fibers, grooved fibers, cactus‐like fibers, tree‐like fibers, ribbon fibers, rough fibers, beaded fibers, and butterfly wings fibers) leads to enhancing or changing their properties …”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that maneuvering the surface morphology of electrospun fibers (eg, crimped fibers, wrinkled fibers, porous fibers, grooved fibers, cactus‐like fibers, tree‐like fibers, ribbon fibers, rough fibers, beaded fibers, and butterfly wings fibers) leads to enhancing or changing their properties …”
Section: Introductionmentioning
confidence: 99%
“…The use of polymer electrospun nanofibers for incorporating photocatalyst nanoparticles through different fabrication methods is a promising strategy to provide enough reactive sites and avoid nanoparticles from being wasted during the separation process [31][32][33][34]. Because of extra-long one-dimensional structures, nanosized diameters and good flexibility, polymer electrospun nanofibers are considered to be good supports for immobilizing nanoparticles [35,36]. PAN is a widely used polymer for the fabrication of nanofibers using simple and versatile electrospinning techniques because of its good processability, environmental stability and low density.…”
Section: Introductionmentioning
confidence: 99%
“…In that context, a very powerful and scalable method to produce nanofibers is electrospinning. This technique has been widely used in the last years because is relatively simple, economical, and versatile [20,21]. By selecting the optimal synthetic parameters, a wide variety of polymeric solutions could be used to prepare micro or nano materials.…”
Section: Introductionmentioning
confidence: 99%